Effect of Mindfulness Dhikr Breathing Therapy for Insomniacs on Quality of Life: A Randomized Controlled Trial - Setiyo Purwanto; Mahadir Ahmad; Zaini Said; Nisa Rachmah Nur Anganthi; Siti Zulaekah (Islamic Guidance and Counseling Journal, 2023)
This study aims to investigate the impact of mindfulness dhikr breathing therapy on the quality of life among individuals suffering from insomnia. This study involved forty-seven participants who were randomly allocated into three groups: mindfulness dhikr breathing (MDB), progressive muscle relaxation (PMR), and a Control group that did not receive any treatment. The participants were adults aged between 20 and 35 years, with 78.72% female and 21.28% male. Among the participants, 91.49% were students, while 8.51% were employees. The treatment period spanned 28 days, with four sessions conducted every Saturday. The primary outcome measure was the assessment of the quality of life, which was evaluated using a valid and reliable World Health Organization-Quality of Life (WHOQOL) BREF questionnaire. Statistical analysis involved the utilization of various tests, including paired t-tests, Wilcoxon tests, independent t-tests, Mann-Whitney tests, and one-way ANOVA tests. Significant differences were observed in the effects of the three intervention groups on overall QoL (p=.035), general health (p=.008), physical well-being (p=.006), psychological well-being (p=.000), and environmental factors (p=.007), except for the social relationship domain (p=.269). However, no significant differences were found in the effects of MDB and PMR treatments on overall QoL (p=.922), general health (p=.756), physical well-being (p=.497), psychological well-being (p=.883), social relationships (p=.569), and environmental factors (p=.618). In conclusion, mindfulness dhikr breathing therapy has demonstrated its effectiveness in enhancing the quality of life for individuals with insomnia. It holds the potential to serve as a suitable alternative to commonly used insomnia therapies, such as progressive muscle relaxation.